Long length of hospital stay in children with medical complexity. Issue 11 (5th July 2016) - Gold, Jessica M.; Hall, Matt; Shah, Samir S.; Thomson, Joanna; Subramony, Anupama; Mahant, Sanjay; Mittal, Vineeta; Wilson, Karen M.; Morse, Rustin; Mussman, Grant M.; Hametz, Patricia; Montalbano, Amanda; et al.
Abstract : BACKGROUND: Hospitalizations of children with medical complexity (CMC) account for one‐half of hospital days in children, with lengths of stays (LOS) that are typically longer than those for children without medical complexity. The objective was to assess the impact of, risk factors for, and variation across children's hospitals regarding long LOS (≥10 days) hospitalizations in CMC. METHODS: A retrospective study of 954, 018 CMC hospitalizations, excluding admissions for neonatal and cancer care, during 2013 to 2014 in 44 children's hospitals. CMC were identified using 3M's Clinical Risk Group categories 6, 7, and 9, representing children with multiple and/or catastrophic chronic conditions. Multivariable regression was used to identify demographic and clinical characteristics associated with LOS ≥10 days. Hospital‐level risk‐adjusted rates of long LOS generated from these models were compared using a covariance test of the hospitals' random effect. RESULTS: Among CMC, LOS ≥10 days accounted for 14.9% (n = 142, 082) of all admissions and 61.8% (13.7 billion) of hospital costs. The characteristics most strongly associated with LOS ≥10 days were use of intensive care unit (ICU) (odds ratio [OR]: 3.5, 95% confidence interval [CI]: 3.4‐3.5), respiratory complex chronic condition (OR: 2.7, 95% CI: 2.6‐2.7), and transfer from another medical facility (OR: 2.1, 95% CI: 2.0‐2.1). After adjusting for severity, there was significant ( P < 0.001) variation in the prevalence of LOS ≥10 days for CMC across children's hospitals (range, 10.3%–21.8%). CONCLUSIONS: Long hospitalizations for CMC are costly. Their prevalence varies significantly by type of chronic condition and across children's hospitals. Efforts to reduce hospital costs in CMC might benefit from a focus on prolonged LOS. Journal of Hospital Medicine 2016;11:750–756. © 2016 Society of Hospital Medicine